Advancements in Data Collection Methods: Online Surveys, Interviews, and Beyond - Debnath, Mintu (AG Volumes, 2025)
After a well-designed study, data is the primary source of information required for studying a research topic. Data collection is essential because without the precise information obtained, research cannot be carried out. In this article review the various literature’s study on advancements in data collection methods. It concluded that advancements in online survey and interview methods have revolutionized data collection, especially in the wake of the COVID-19 pandemic. The rise of digital tools and self-recorded video statements has enabled multimodal data capture, enhancing both qualitative and quantitative research. Online platforms offer cost-effective, wide-reaching, and convenient solutions for collecting accurate data. While some areas of survey research adopt innovations cautiously, others embrace rapid transformation driven by digital engagement and user preferences. As internet usage grows, online data collection continues to evolve, supporting dynamic research strategies and fostering a more agile, visually oriented, and globally connected research environment.